Impact of overweight or obesity trajectory on health expenditure in Korea. (20th June 2019) - Kim, T H; Han, E
Abstract: Background: This study aimed to identify the effect of the overweight or obesity (OWOB) trajectory on current health care expenditure in South Korea. Methods: Ten years of publicly released data (2002–12) were obtained in 2016 from a retrospective cohort of National Health Insurance System claims. This study included 51, 844 adults (aged 30–59 years in 2002) and 21, 196 elderly adults (aged ≥ 60 years in 2002). Results: Compared with adults who maintained normal weight (NW), higher yearly total health expenditures were estimated for adults who lost weight over the 10-year period: by 11.5% (95% confidence interval (CI): 0.18–22.96%) when changing from NW to underweight (UW) and 6.2% (95% CI: 0.47–12.01%) from OWOB to UW/NW. Elderly adults had higher health expenditures when they lost weight by 14.0% (95% CI: 0.37–27.70%) from NW to UW and 6.8% (95% CI: 0.13–13.51%) from OWOB to UW/NW compared with when they maintained NW. Conclusions: These findings indicate the importance of early intervention to control OWOB, particularly because people in late adulthood have greater health care needs for reasons other than OWOB.